IMPLEMENTASI PENDEKATAN KONSELING ISLAM DALAM MENGATASI PROBLEMATIKA AKHLAK PESERTA DIDIK DI MADRASAH ALIYAH : STUDI KUALITATIF (VARIABEL X : PENDEKATAN KONSELING ISLAMI, VARIABEL Y : PROMBLEMATIKA AKHLAK PESERTA DIDIK) - Lusia Juniarti; Nadila Farahita; Hartini; Beni Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Problems with students' morals in Madrasah Aliyah, such as low discipline, lack of respect for teachers, dishonest behavior, and conflicts between students, are challenges that require handling through guidance and counseling services that are not only oriented towards psychological aspects, but also spiritual aspects. This study aims to analyze the implementation of the Islamic Counseling approach in addressing the problems of students' morals in Madrasah Aliyah. The study used a library research method with a descriptive qualitative approach. Data were obtained from various library sources in the form of books, journals, and relevant research results in the period 2017–2023. Data analysis was carried out using content analysis techniques through the processes of identification, classification, and synthesis of the reviewed literature. The results of the study indicate that the Islamic Counseling approach is effective in helping the formation of students' personalities and morals through the integration of the values of the Qur'an and Sunnah in the counseling process. The success of its implementation is influenced by the assessment of students' needs, systematic guidance and counseling program planning, and the competence of guidance and counseling teachers in integrating Islamic values into counseling services. Thus, Islamic Counseling can be a relevant and effective alternative approach to fostering students' morals and supporting the achievement of Islamic education goals in Islamic Senior High Schools (Madrasah Aliyah).